Digitalization of small and medium-sized enterprises and economic growth: Evidence for the EU-27 countries - Jarosław Brodney; Magdalena Tutak (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Successful implementation of digital solutions in a given region or country significantly depends on the implementation of this process by Small and Medium-Sized Enterprises (SMEs). This problem is very well understood in the European Union, where actions are being taken to accelerate this process and build a sustainable and competitive knowledge-based economy. This article addresses this issue by conducting a study of the digital maturity of SMEs among the EU-27 countries. The aim of the study was to determine the level of digital maturity of SMEs in the EU-27 countries as well as whether and how the economic parameters of individual EU countries affect the process of SME digitalization. The adopted objectives determined the developed research methodology and the applied methods. The research was based on data from the Eurostat database, on the basis of which 11 indicators characterizing technologies and digital solutions identified with the Industry 4.0 concept were specified and adopted for the study. The entropy-based Evaluation based on distance from average solution (EDAS) method was used to assess the EU countries in terms of the level of digital maturity of SMEs, and the Principal Component Analysis (PCA) method was used to analyze similarities between these countries in terms of technologies implemented in SMEs. On the other hand, to determine a relationship between the digital maturity index (digitalization) and the basic economic parameters of the economy, two nonparametric tests (Spearman and Tau Kendall) were utilized. Based on the determined digital maturity index, the EU-27 countries were evaluated in terms of the level of digital maturity of SMEs, dividing them into four groups. The results showed large discrepancies between individual EU-27 countries and between the old (EU-14) and the new (EU-13) EU countries in terms of SMEs digitalization. These results should be widely used to develop a digitalization strategy for the EU economy and policies to improve the degree of digitalization, especially in countries lagging in this area. The universality of the developed methodology creates wide opportunities for its use to study other countries and regions worldwide.
Keywords: 650; digitalization; economic growth; SMEs; EU-27; entropy-EDAS method; PCA method